Identification, characterization and application of the potential trichoderma species locally isolated from Lahad Datu, Sabah - Nur Shafawati Saili (2016)
Specifics trains of Trichoderma species have been commercially applied as biocontrol agents against several plant pathogenic fungi due to their production of antifungal metabolites, competition for nutrients and space, and mycoparasitism. The main aim of this study was to identify the specific potential of Trichoderma strains from an oil palm plantation in Lahad Datu for the application in the biocomposting of oil palm empty fruit bunches. This compost able to enhanced plant growth performance and also produced high yield production. Generally, compost is not only a good biofertilizer but also a good biocontrol agent against soil-borne pathogens. Isolation of Trichoderma species from soil was done using dilution technique. A total of 138 colonies of fungus found, and only 97 isolates were physically identified as Trichoderma species. Apart from that, only 52 Trichoderma isolates were further identified based on the morphological characteristics and molecular data analysis. From the results, all 52 isolates were belong to eight Trichoderma species namely Trichoderma asperel/um, T. harzianum, T. koningiopsis, T. hamatum, T. theobromicola, T. erinaceum, T. viride and Hypocream e/anomagnaN. ext, the lignocellulolytica ctivitieso f all isolates were studied based on their ability to degrade cellulose, lignin and starch and the best potential strains were selected as the decomposers. Strains 2H, 5D and 1012 were found to give the largest halo zone in the order of 4.40 ± 0.46 cm for cellulose, 4.93 ± 0.06 cm for lignin and 7.47 ± 0.15 cm for starch, respectively. Based on these results, two strains (11B and SICCI) were selected for the composting of oil palm fibre. Over the four weeks of the composting period, analysis of pH of the compost was found to be slightly alkaline at the earlier stage and slowly become acidic. The temperature recorded was almost the same being the 24°C during the laboratory assay. Field experiments were done to test the effectiveness of the compost for 15 weeks by using chilli plants and two types of compost (Compost A and Compost B) together with a control group. Based on the results, Trichoderma propagules were found dominant with 72% abundancy in soil when compared to the other fungi. Compost A showed better results in length (90 cm), number of leaves (95.5), stem diameter (0.8 cm), branching root development, flower formation (21 during week 13), and yield of Chilli (58) compared to compost B and control. However, chili tree mixed with compost B had an average higher branch formation (7.8), higher percentage of moisture in plant (58.93 %) and longer root development (32.6 cm). Analysis of soil electrical conductivity showed it to be 50.40 µS/cm for compost A, 42.10 µS/cm for compost B and 40.11 µS/cm for the control, respectively. Higher CN ratio was found in compost A and B (3.21: 0.26,3.18: 0.26) as compared to control (2.71: 0.26). Analysis on week eight showed the ratio of NPK to be in the order, compost A (4.30) > compost B (2.79) > control (1.55). To conclude, either by using compost A or compost B, composting of oil palm fibres shows a great potential for application in agricultural fields to improve soil fertility, soil texture, enhance plant growth and high yield of production.